Culture as praxis - Bauman, Zygmunt, 1925-2017 (Theory, culture & society (Unnumbered), 1999)
Bauman seeks to classify the meanings of culture, rather than simply describing it as other accounts have done. In his proposal that culture is inherently ambivalent he distinguishes between culture as a concept, as a structure and as praxis.